Subverting Patriarchy as Gender Politics: A Feminist Perspective on the Narrative of Women’s Performativity - Paudyal, Ganga Ram (Academia Journal of Humanities & Social Sciences, 2025)
This paper explores the perspective of gender subversion for the liberation and the independence of women. The issue concerning constructed gender trouble and identity is discussed and analyzed, using the insights of Judith Butler whose performativity has been considered the theoretical lens that gender is not an inherent identity and can be subverted. To discuss this issue, Caryl Churchill’s play Top Girls has been undertaken as a primary source of information for textual analysis. The play is performed by all female cast where female characters play multiple roles to contrast and show the transition in gender roles. The objective of this paper is to portray the subversive character of women who have undergone repression, suffering, sacrifice, and compromise in a capitalist and individualist society. Their resistance to patriarchal norms has made them independent rather than obeying the supremacy of males. For instance, the celebration organized by Marlene with historical and legendary women reflects both the challenges faced by women and their success as career and independent women. As a qualitative approach of study, it reviews some articles and books concerning Churchill and her play as secondary sources of information. The play as a primary source has provided data and information how the gender roles are challenged and independence of female characters is reflected. The findings of this study indicate that the play attempts to subvert the traditional gender role by reflecting Marlene as a successful and independent female character.